(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Feminism has been subtly handled in the massive work of English novels in India. Feminism is defined as cultural, economic and political movements that are focused towards establishing legal protection and complete equality for the women. In Indian writing feminism has been used as a modest attempt for evaluating the real social scenario as far as women are concerned. The Indian English novelists use oriental approaches of feminism. There are several novels in English literature of India that aptly portrays the actual status of the women in Indian societies. However, the modern aged women have realized that they are equally competent like the men and those they are not helpless. Unlike the past when men were considered as the sole bread earners, in today’s age, women too have become direct money earners of any household.